2018
DOI: 10.5505/ktd.2018.94546
|View full text |Cite
|
Sign up to set email alerts
|

Comparıson Of The Results Of Pemberton And Salter Osteotomıes Applıed In Developmental Dysplasıa Of The Hıp

Abstract: C Co om mp pa ar ri is so on n o of f t th he e R Re es su ul lt ts s o of f P Pe em mb be er rt to on n a an nd d S Sa al lt te er r O Os st te eo ot to om mi ie es s A Ap pp pl li ie ed d i in n D De ev ve el lo op pm me en nt ta al l D Dy ys sp pl la as si ia a o of f t th he e H Hi ip p

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…The prevalence of AVN in the 4 -8 years group ranges between 3% and 60% (8). In a systemic review of comparative studies, they reported that the complication rate for Salter innominate osteotomy was 9.4% and AVN was the most common complication (23) (27). In our study, AVN of the femoral head was observed in two patients; according to Bucholz and Ogden's classification, one was Type 1 and one was Type 3 AVN.…”
Section: Discussionsupporting
confidence: 48%
“…The prevalence of AVN in the 4 -8 years group ranges between 3% and 60% (8). In a systemic review of comparative studies, they reported that the complication rate for Salter innominate osteotomy was 9.4% and AVN was the most common complication (23) (27). In our study, AVN of the femoral head was observed in two patients; according to Bucholz and Ogden's classification, one was Type 1 and one was Type 3 AVN.…”
Section: Discussionsupporting
confidence: 48%